Blue Light Sensing in Listeria monocytogenes Is Temperature-Dependent and the Transcriptional Response to It Is Predominantly SigB-Dependent - Dorey, Amber L.; Lee, Bo-Hyung; Rotter, Bjorn; O’Byrne, Conor P. (Frontiers in Microbiology, 2019)
Listeria monocytogenes is an important food-borne pathogen that is tolerant to many of the stresses commonly used during food preservation. Outside the host, the bacterium has a saprophytic lifestyle that includes periodic exposure to solar irradiance. The blue component of this light is known to influence the activity of the stress-inducible sigma factor Sigma B (σB). In this study, the influence of temperature and growth phase on the response of L. monocytogenes to blue light was investigated and the global transcriptional response to blue light was elucidated using an RNAseq-based approach. Stationary phase cells were found to be significantly more resistant to killing by blue light (470 nm) than exponential phase cells. Temperature also had a marked effect on blue light resistance with cells cultured at 37°C being much more sensitive than cells grown at 30°C. The role of σB in light tolerance was confirmed but this effect was observed only at 30°C. σB activation by blue light was assessed by measuring the transcriptional response of known σB-dependent genes (sigB, lmo2230, and opuCA) to light. The transcripts were induced by blue light only at 30°C suggesting that blue light fails to activate σB at 37°C. The light-induced transcription at 30°C was dependent on a functional blue light sensor, Lmo0799 (which we rename herein as RsbL). A transcriptomic analysis of the response to sub-lethal levels of blue light found that the changes in transcription were almost entirely σB-dependent. A mutant where the light sensing mechanism of RsbL was inactivated through an amino acid substitution (Cys56Ala) was found to have an attenuated response to blue light, but residual activation of σB-dependent genes suggested that alternative routes for activation of σB by light are likely to exist. Overall, the study highlights the central role of σB in the response of this pathogen to visible light and further shows that light sensing is absent at temperatures that exist within the mammalian host.